Practical Aspects of Declarative Languages 16th International Symposium, PADL 2014, San Diego, CA, USA, January 19-20, 2014, Proceedings - Flatt, Matthew; Guo, Hai-Feng.; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2014)
This book constitutes the refereed proceedings of the 16th International Symposium on Practical Aspects of Declarative Languages, PADL 2014, held in SanDiego, CA, USA, in January 2014, co-located with POPL 2014, the 41st Symposium on Principles of Programming Languages. The 15 revised papers presented were carefully reviewed and selected from 27 submissions. They cover a wide range of topics related to logic and functional programing, including language support for parallelism and GPUs, constructs and techniques for modularity and extensibility, and applications of declarative programming to document processing and DNA simulation.
A Prescription for Safely Relaxing -- Partial Type Signatures for Haskell -- The F# Computation Expression Zoo -- Abstract Modular Inference Systems and Solvers -- Sunroof: A Monadic DSL for Generating JavaScript -- Compiling DNA Strand Displacement Reactions Using a Functional Programming Language -- Two Applications of the ASP-Prolog System: Decomposable Programs and Multi-context Systems -- Towards Modeling Morality Computationally with Logic Programming -- A Declarative Specification of Giant Number Arithmetic -- Embedding Foreign Code -- Exploring the Use of GPUs in Constraint Solving -- On the Correctness and Efficiency of Lock-Free Expandable Tries for Tabled Logic Programs -- Typelets — A Rule-Based Evaluation Model for Dynamic, Statically Typed User Interfaces -- Expand: Towards an Extensible Pandoc System -- Generic Programming.
Keywords: Programming languages (Electronic computers).; Computer programming; Computer logic; Software engineering; Programming Languages, Compilers, Interpreters; Programming Techniques; Logics and Meanings of Programs; Software Engineering